Odissey Concept; Reformulasi Penyelenggaraan Jaminan Sosial Tenaga Kerja sebagai Strategi Mewujudkan Kesejahteraan Tenaga Kerja ASEAN yang Terintegrasi - Rossa Wahyu Ningrum; Dyah Alif Suryaningsih; Fazal Akmal Musyarri (CV Rewang Rencang, 2020)
This paper explains the social security of ASEAN employees. Labor as a support for the improvement of development and economic growth in a country is entitled to social security. In Indonesia, the social security of the workforce itself is protected by Indonesian Employees Insurance which is incorporated in one insurance consortium. The basis is because the consortium is a social security private insurance instead of prioritizing Profit Oriented rather than guaranteeing the continuity of the fate of the workforce starting from before departure to guarantee the safety of migrant employees back to their home countries. There are some obstacles that are still an unresolved scourge of labor problems, ranging from difficulties in the management of insurance claims because employees have to return to their home countries to take care of insurance claims and insurance claims by consortiums that are not maximal. So the author made the idea of BPJS Go International which is a meltdown from insurance consortiums in Indonesia. In addition, the author also made an idea about the concept of the fulfillment of integrated and integrated social security for ASEAN employees based on Odissey Concept.